ANTEGRADE LASER PAPILLOTOMY UNDER THE CONTROL OF VIDEO CHOLEDOCHOSCOPY IN PATIENTS WITH STENOSIS OF THE LARGE DUODENAL PAPILLA COMPLICATED WITH MECHANICAL JAUNDICE - N. V. Levchenko; V. V. Khryachkov; R. R. Shavaliev; D. P. Kislitsin (Исследования и практика в медицине)
Purpose. To analyze the efficacy of the YAG:Ho laser in laparoscopic treatment of large duodenal papilla (LPA) stenosis complicated by mechanical jaundice.Patients and methods. The work is based on a prospective analysis of 31 patients undergoing treatment in the KhMAO-Ugra BU “NyaganDistrictHospital”. To perform antegrade laser papillotomy, a laser setup equipped with high-energy YAG: Ho laser, endovideosurgical complexes and a fibrocholedochoscope was used. During laparoscopic cholecystectomy, intraoperative choledochoscopy and antegrade laser papillotomy were performed.Results. Laser papillotomy was successfully performed in 31 (100%) patients with benign stenosis of LDP, among them in 15 patients (48.4%) the stenosis of LDP was combined with choledocholithiasis, which was detected intraoperatively in 9 (29.0%) cases. For optimal conduction of choledochoscopy, a guide device for a choledochoscope has been proposed (RF patent for utility model No. 149055 dated May 12, 2014).All surgical interventions, including lithotripsy, were performed laparoscopically, there was no indication for conversion.Conclusion. The received results show high efficiency of the applied technique, absence of complications and lethal outcomes. Antegrade laser papillotomy is effective even in those situations where endoscopic retrograde papillosphincterotomy is technically difficult or impracticable.